Identification of some alkaloids in datura stramonium (Saikaran, Jimson weed) - Ibrahim, Fatima Babiker Dafa-Alla; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Jamal, Parveen (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
This study aims at investigating the presence of alkaloids and other chemical constituents in Datura stramonium (Saikaran, Jimson weed). All parts of the plant were dried, crushed and then underwent extraction by soxhlet and maceration methods. The solvents used in these methods were normal hexane (nonpolar) and ethanol (polar). TLC and FTIR techniques were used to analysed the chemical components of jimson weed. The results showed the presence of hyoscine in all plant parts while atropine in the seeds only. The best separation was found to be when the solvent system was acetone: water: ammonia (90:07:03). Maceration method is the best procedure for extraction, in addition, it is cheap.